LGG-31. CHARACTERIZING TEMPORAL GENOMIC HETEROGENEITY IN PEDIATRIC LOW GRADE GLIOMAS: ANALYSIS OF AN EXPANDED MULTI-INSTITUTIONAL COHORT WITH 101 PAIRED TUMOR SAMPLES. (4th December 2020) - Lazow, Margot A; Schafer, Austin; DeWire-Schottmiller, Mariko D; Lane, Adam; Boué, Daniel R; Osorio, Diana S; Finlay, Jonathan L; Wright, Erin; Rush, Sarah; Hoffman, Lindsey M; Reuss, Jamie; Hummel, Trent R; et al.
Abstract: INTRODUCTION: Recent discoveries have provided valuable insight into the genomic landscape of pediatric low grade gliomas (LGGs) at diagnosis, facilitating molecularly targeted treatment. However, little is known about their temporal and therapy-related genomic heterogeneity. An adequate understanding of the evolution of pediatric LGGs' genomic profiles over time is critically important in guiding decisions about targeted therapeutics and diagnostic biopsy at recurrence. METHODS: Fluorescence in situ hybridization, mutation-specific immunohistochemistry, and exome analyses were performed on paired tumor samples from primary diagnostic and subsequent surgeries. RESULTS: 101 tumor samples from 48 patients (43 with 2 specimens, 5 with 3 specimens) from 3 institutions underwent testing. BRAF fusion and BRAF V600E status were conserved in 100% and 97% of paired specimens, respectively. No loss or gain of IDH1 mutations or FGFR1, NTRK2, MYB, or MYBL1 rearrangements were detected over time. Histologic diagnosis remained the same in all tumors, with no acquired H3K27M mutations or malignant transformation. CDKN2A deletions were acquired in 7 patients (including 3 who received chemotherapy [2 with temozolomide] and 1 who received radiation), and were associated with a trend toward shorter time to progression (median: 5.5 vs. 13.0 months [p=0.08]). CONCLUSIONS: Most targetable genetic alterations in pediatric LGGs, including BRAF alterations, are conserved at recurrence and following chemotherapy or radiation. However, CDKN2A deletion acquisition was demonstrated and may define a higher risk group. Given potential for targeted therapies for tumors acquiring CDKN2A deletions, performing a biopsy at recurrence may be indicated in certain patients, especially those with rapid progression.